(untitled) (Ameghiniana, 2014)
A new genus and species, Australoproctafleaglei, from the Colhuehuapian Age (Early Miocene), Sarmiento Formation, is described. Molar morphology shows an incipient sigmoid pattem as in the Santacrucian genus Scleromys. Upper premolars are pentalophodont but without a differentiated hypocone-hypoflexus. The pattem of the molars and premolars seems to be structurally ancestral to Scleromys but not to Incamys (from Deseadan of Bolivia) nor to Neoreomys (Santacrucian). Patagonian dasyproctids could have arisen from an Australoprocta-like ancestor, separately from Incamys and living dasyproctids.